RESERVOIR CHARACTERIZATION USING EXTENDED ELASTIC IMPEDANCE INVERSION METHOD WITH LAMBDA-RHO AND MU-RHO PARAMETERS IN âNOPALâ FIELD, NORTH EAST JAVA BASIN - Naufal Taajliefan, Ammardra
The Kujung Formation in the "Nopal" field is one of the oil and gas producing fields located in the North East Java Basin. This formation is composed of carbonate rocks with intercalated shales. Due to its complexity, it is necessary to conduct research on the lateral distribution of porous carbonate reservoir and the distribution of hydrocarbons that fills this field. For this reason, we need elastic parameters that are sensitive to lithology and the presence of fluids. In addition, it is necessary to apply a method that can describe the elastic parameters in the reservoir zone. In this research, elastic parameters were used, namely mu-rho which is sensitive to lithology so that it can be used to see porous carbonate rocks, and lambda-rho which is sensitive to the presence of fluids so that it can be used to see the hydrocarbons that fills the reservoir. The Extended Elastic Impedance (EEI) method, which is a method that can invert the reflectivity volume of the elastic parameter, is very suitable to be used in this research This method is more suitable to use than the Acoustic Impedance (AI) method which uses the p-impedance parameter, because this parameter still cannot separate lithology and fluid. From the resulting EEI reflectivity volume, it will be inverted using the seismic inversion sparse spike linear programming method. Then from the results of inversion and slicing, it was found that the "Nopal" field has porous carbonate rocks which are estimated because the high area in this field is a paleo high structure that was exposed to the surface and experienced leaching, and also there is a zone that is proven to be filled with hydrocarbons at the peak of the anticline. However, the analysis of the log data shows that there are still zones that may be filled with hydrocarbons, so further tests need to be carried out to prove the presence of hydrocarbons in this zone.